Effect of educational intervention on midwives’ skills in utilising uterine balloon tamponade for managing postpartum haemorrhage in Ogun State, Nigeria - Foyekemi Adamu-Adedipe; Olayinka Onasoga (Babcock University Medical Journal)
Objective: Studies demonstrated the cost-effectiveness of Uterine Balloon Tamponade (UBT) in reducing PPH. However, in Ogun State, Nigeria studies revealed midwives’ inadequate skills to utilise UBT. Therefore, this study assessed the effect of the intervention on midwives’ skills in utilising UBT for managing PPH at Primary Healthcare Centres (PHC), Ogun State, Nigeria.